"Beauty is in the eye of the beholder" : a comparative study of Chinese & Indian Singaporean women's ideals of beauty. - Shivali Dayanand Nayak. (2010)
Beauty has such great significance in our society today, especially for women and that has spurred people to go to great lengths to achieve perfection that has often been representative of the White ideal beauty. I focus on the cultural aspects of beauty, by speaking to Chinese and Indian women in Singapore, in order to find out how they define beauty and how their influences affect them in defining beauty. By conducting in-depth interviews with these women, I found that beauty is an agency for these women who use beauty to assimilate into or differentiate themselves from society. In analyzing how women deal with hair, skin, body size and dressing, I show how Singaporean women have found the multicultural environment of Singapore useful in defining their own beauty standards. I also show how we are moving forward from one particular ideal of beauty and toward a more accepting, diverse ideal of beauty.